Diseño conceptual de un proceso de extracción y purificación de melanina a partir de imagos de la mosca soldado negra (Hermetia Illucens) dentro del esquema de biorrefinería. (2024)
In this article, the study of melanin in the imago of the black soldier fly (Hermetia illucens) is developed. This species has been the subject of study in different fields of science due to its remarkable biological characteristics. Melanin, a pigment used in different industries such as pigments and dyes, UV protection in materials, bio medicine and cosmetics among others. Therefore, the present project performs the characterization and extraction of melanin in black soldier fly (Hermetia illucens) imagos using green chemistry methods and compares them with the performance of conventional methods. The study is composed of two complementary approaches: a literature review consolidating current knowledge on melanin in Hermetia illucens and the implementation of standardized methods in the laboratory for melanin extraction and purification from fly imagos. A highlight of this research is the application of green chemistry principles, which focuses on minimizing the environmental impact of the operations, making the process more sustainable.